Islamicity Performance Index in Measuring the Financial Performance of Indonesian Islamic Banks - Safitri, Novita; Imsar, Imsar; Syakir, Ahmad (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
The rapid growth of Islamic banking makes it necessary to measure the performance of Islamic banks using Islamic values as the basis. One method that can be used to evaluate the performance of Indonesian Islamic banks is the Islamicity Performance Index (IPI) method. This study aims to measure the financial performance of Indonesian Islamic Banks. This research design uses a quantitative descriptive approach. The data used in this study is the ratio of profit sharing ratio, zakat performance ratio, equitable distribution ratio, Islamic income vs non Islamic income ratio, Islamic investment vs Non- Islamic investment Ratio taken from the annual financial statements of Bank Syariah Indonesia Syariah in 2021-2024. The results of this study indicate that the performance of Bank Syariah Indonesia has not met all sharia standards. Of the 5 IPI ratios used, only 3 ratios consistently meet sharia criteria, namely the profit sharing ratio, Islamic investment vs. Non- Islamic investment ratio and Islamic income vs. Non- Islamic income ratio. While 2 ratios namely Equitable Distribution Ratio (EDR) and Zakat Performance Ratio (ZPR) do not meet the sharia criteria of IPI because there are still elements that are not in accordance with sharia principles.